Measurement of sample temperatures under magic-angle spinning from the chemical shift and spin-lattice relaxation rate of (79)Br in KBr powder - Thurber, Kent R. (2008)
Accurate determination of sample temperatures in solid state nuclear magnetic resonance (NMR) with magic-angle spinning (MAS) can be problematic, particularly because frictional heating and heating by radio-frequency irradiation can make the internal sample temperature significantly different from the temperature outside the MAS rotor. This paper demonstrates the use of (79)Br chemical shifts and spin-lattice relaxation rates in KBr powder as temperature-dependent parameters for the determination of internal sample temperatures. Advantages of this method include high signal-to-noise, proximity of the (79)Br NMR frequency to that of (13)C, applicability from 20 K to 320 K or higher, and simultaneity with adjustment of the MAS axis direction. We show that spin-lattice relaxation in KBr is driven by a quadrupolar mechanism. We demonstrate a simple approach to including KBr powder in hydrated samples, such as biological membrane samples, hydrated amyloid fibrils, and hydrated microcrystalline proteins, that allows direct assessment of the effects of frictional and radio-frequency heating under experimentally relevant conditions.